Patient centred medical home (PCMH) and patient‐practitioner orientation: Is there a relationship?. Issue 5 (6th May 2018) - Khan, Shamima; Spotts, Harlan E.; Lindblad, Peter C.; Spooner, Joshua J.
Summary: Background: The patient‐centred medical home (PCMH) and utilisation of a patient‐centred care approach have been promoted as opportunities to improve healthcare quality while controlling expenditures. Objectives: To determine the penetration of PCMH within physician practices, and to evaluate physician attitudes towards patient‐practitioner orientation. The ultimate objective was to explore relationships between the patient‐practitioner orientation of respondents and the presence of PCMH elements within their practice. Methods: A survey instrument was developed following a comprehensive literature review. Lead physicians practicing in four states were surveyed. Results: The adjusted response rate was 26.7%. Responses indicated increased utilisation of PCMH elements (electronic medical records, e‐mail and telephone consultations, and physician performance monitoring and feedback) compared with previous research. Within a logistic regression model, medical school graduation year (1990 or later >prior to 1990), practice size (group >solo), and percentage of time allocated to patient care (less >more) were significant predictors of working in a high PCMH alignment setting. Physician and practice characteristics did not predict the level of patient‐practitioner orientation, though rural physicians were more patient‐centred than urban physicians. A non‐linear correlation between patient‐practitioner orientation and the likelihood of practicing in a low or high PCMH‐aligned practice was observed. Conclusions: There is a non‐linear correlation between patient‐practitioner orientation and the likelihood of a physician practicing in a low or high PCMH‐aligned practice. The ability of a physician to work in a PCMH setting or practicing patient‐centred care can go beyond a physician's aspirations to work and practice in that manner.